2017
DOI: 10.1177/0040517517693978
|View full text |Cite
|
Sign up to set email alerts
|

The effect of three-layer weft knitted material structure and composition upon performance properties

Abstract: The effect of three-layer weft knitted spacer material content and structure upon the characteristics of uniaxial tension, biaxial punching before and after fatigue punching, and at multi cycle low-stress (wearing level) punching were investigated. Three different spacer structures were knitted using four types of the same 20 tex linear density spun yarns. For three-layer weft knitted samples, innovative fibers, which are used in the production of functional clothing, were selected: Coolplus® 100% polyester (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…A systematic study of mechanical behaviour and the influence of the structure factors is necessary, which would allow proper choice of the fabric structure to obtain high-performance 3D knitted fabrics. Meanwhile, little research has been done to study the effect of yarn content and knitted structure type upon three-layer weft-knitted spacer fabric mechanical behaviour [29]. Based on the existing literature, it has been found that the relationships between the knitted structures and the properties of the weft-knitted spacer fabrics are still not established [30].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic study of mechanical behaviour and the influence of the structure factors is necessary, which would allow proper choice of the fabric structure to obtain high-performance 3D knitted fabrics. Meanwhile, little research has been done to study the effect of yarn content and knitted structure type upon three-layer weft-knitted spacer fabric mechanical behaviour [29]. Based on the existing literature, it has been found that the relationships between the knitted structures and the properties of the weft-knitted spacer fabrics are still not established [30].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it possesses less structural integrity and inferior mechanical properties than WKSF. 23,24 Most properties of weft-knitted spacer fabric are similar to WKSF, but limited researches have been launched with regard to this particular fabric. In recent years, compressive characteristics, air permeability, water vapor permeability and thermal conductivity of weft-knitted spacer fabric are often explored for cushioning applications and wound dressings.…”
Section: Knitted Spacer Fabricmentioning
confidence: 99%